An efficient regression testing approach for PHP web applications: a controlled experiment. (August 2014) - Do, Hyunsook; Hossain, Md.; Bertolino, Antonia; Labiche, Yvan
SUMMARY Companies that provide web applications often encounter various security attacks and frequent feature‐update demands from users, and when these needs arise, companies need to fix security problems or upgrade the application with new features. These fixes often involve small patches or revisions, but still, testers need to perform regression testing on their products to ensure that the changes have not introduced new faults. Performing regression testing on the entire product, however, can be very expensive, and it is not a viable solution for companies that need a short turnaround time to release patches. One solution is focusing only on the code areas that have been changed and performing regression testing on them. By doing this, companies can provide quick patches more dependably whenever they encounter security breaches. In this paper, the authors proposed a new regression testing approach that identifies the affected areas by code changes using impact analysis and generates new test cases for the impacted areas by changes using program slices. To facilitate the approach, the researchers implemented a Hypertext Preprocessor (PHP) Analysis and Regression Testing Engine (PARTE) and performed a controlled experiment using five open source web applications with multiple versions. The results showed that this approach is effective in reducing the cost of regression testing for a frequently patched web application, and exposed ways in which that effectiveness can vary with application characteristics and versioning frequencies. Copyright © 2014 John Wiley & Sons, Ltd.